The Potential of Micro-Dictum Preparation in Surface Water Reclamation Subject to Strong Anthropogenic Pressure - Kupiec, Jerzy Mirosław (Water (Basel), 2024)
The aim of this research was to analyze the potential of e micro-dictum preparation containing compositions of beneficial microorganisms using this product in surface water reclamation. The experiments were carried out in 2016. The scope of this research included the analysis of the physical and chemical properties of a solid preparation; tests of the microbiological parameters of micro-dictum; an analysis of the spread of microorganisms in the aquatic environment; a study of water quality with the solid preparation; and tests of the formulation in real conditions and its potential in the reclamation of surface waters. Tests on the produced formulation were carried out in the laboratory in containers and under real conditions. Laboratory tests have shown that the analyzed preparation may introduce certain amounts of nitrogen and phosphorus into the water. However, they are not important in the case of water reclamation. Analyses of the micro-dictum preparation showed that the content of lactic acid bacteria in the center of the ball is lower compared to the outer layers. The results describing an increase in the number of lactic acid bacteria correlate with a decrease in pH and oxygen dissolved in the water with the preparation. The tests showed no negative impact on changes in the physical and chemical properties of water at the site of application. Changes in physical parameters were recorded, in particular dissolved oxygen and pH at the bottom, where the greatest microbiological activity occurred.